Determining perceptions of host communities' regarding urban ecotourism - Mashapa, Modjadji Matilda (Vaal University of Technology, 2016)
Tourism has become an essential attribute of modern society that has an effect on the world and its citizens. On the other hand, tourism can also be blamed for an increase in environmental and social stress. Hence the need for a more sustainable tourism industry was advocated; thus the birth of alternative forms of tourism such as urban ecotourism, responsible tourism and community-based tourism. Urban ecotourism has been identified as a method of sustainable tourism that is expected to subsidise to both conservation and development in urban areas. This requires input and cooperation from various stakeholders. One of the most important stakeholders in this process is the local community. Thus, when there is collaboration with host communities in urban ecotourism projects, these projects convert to become community development. These projects such as urban parks are vital assets within the local community as they assist in addressing a broader range of environmental and societal issues. However, these instrumental resources are often ignored, resulting in a loss of potential benefits.
the case of an urban park in Gauteng
Keywords: urban ecotourism; community involvement; perceptions; policies; Ivory Regional Park